The paraoxonase 1 activity and lipid levels in umbilical cord blood and maternal venous blood, and their relations according to birth weight - Kadıoğlu, Berrin Göktuğ; Nalçakan, Aysel; Dilek, Esra (The European Research Journal, 2022)
Objectives: Aim of this study is to find out the clinical relevance of estimating paraoxonase activity of PON1 enzyme, triglyceride (TG), total cholesterol, HDL, and LDL levels in maternal serum and umbilical cord blood according to birth weight. Methods: Venous blood samples were taken from mothers just before birth. Babies were divided into four groups: normal-weight babies, premature babies, low birth weight babies, and postmature babies. The weight of the newborns was measured and cord blood was taken. The samples were looked at HDL, LDL, total cholesterol, triglyceride levels and PON1 activities. We have investigated the paraoxonase activity of the PON1 enzyme. Enzyme activity assay was obtained spectrophotometrically measurement of p‐nitrophenol at 412 nm. Results: Maternal PON1 paraoxonase activity levels in Pre-Term show a significant decrease in cases as compared to other groups. Baby PON1 paraoxonase activity levels are also found to be significantly decreased in cases concerning the Term and Post-Term groups. There was a significant difference in all values the such as baby's weight, TG, Total cholesterol, HDL, LDL and PON1.belonging to babies (p < 0.05). Conclusions: Decreased paraoxonase activity in maternal serum may be considered as an additional risk factor for the development of low birth weight. It appears that PON1 activity plays an important role in infant development and affects birth weight. We think that the paraoxonase activity of the PON1 enzyme in mothers may be a marker in predicting the babies who are at risk in terms of birth weight.